I.YUSUPOVTIŃ EPIKALIQ SHIǴARMALARINDA ROMANTIKALIQ MOTIVTIŃ QOLLANILIW SHEBERLIGI - Qudiyarova, R. (ILIM hám JÁMIYET, 2023)
The article talks about the romantic motif used in the epic works of the Hero of Uzbekistan, the national poet of Uzbekistan and Karakalpakstan I. Yusupov. Romantic motive is one of the issues waiting to be researched in Karakalpak literary studies. The poet’s ability were mentioned about using the romantic motif and his artistic service.